An anatomical substrate for experience-dependent plasticity of the rat barrel field cortex. - Micheva, K D (1995)
The objective of this study was to examine the influence of sensory experience on the synaptic circuitry of the cortex. For this purpose, the quantitative distribution of the overall and of the gamma-aminobutyric acid (GABA) population of synaptic contacts was investigated in each layer of the somatosensory barrel field cortex of rats which were sensory deprived from birth by continuously removing rows of whiskers. Whereas there were no statistically significant changes in the quantitative distribution of the overall synaptic population, the number and proportion of GABA-immunopositive synaptic contacts were profoundly altered in layer IV of the somatosensory cortex of sensory-deprived animals. These changes were attributable to a specific loss of as many as two-thirds of the GABA contacts targeting dendritic spines. Thus, synaptic contacts made by GABA terminals in cortical layer IV and, in particular, those targeting dendritic spines represent a structural substrate of experience-dependent plasticity. Furthermore, since in this model of cortical plasticity the neuronal receptive-field properties are known to be affected, we propose that the inhibitory control of dendritic spines is essential for the elaboration of these functional properties.